Integrating Independence in Early Learning through the Making of Batik Jumputan - Zuleyka, Aisyah; Dewi, Kurnia; Imtihana, Aida (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
This study examines integrating the independence dimension within the Pancasila Student Profile Project through the culturally enriching activity of batik-making, specifically Jumputan Batik, in Indonesia's Merdeka Curriculum. While using a qualitative phenomenological approach, data were collected through observations, interviews, and documentation involving principals, teachers, and students in early childhood education settings. The findings reveal that children demonstrated notable growth in independence, creativity, and resilience, mainly through hands-on activities. The structured project emphasized planning, execution, and evaluation, allowing children to practice self-reliance, adapt to challenges, and collaborate with peers. This study provides actionable insights for educators and policymakers, offering strategies to address identified challenges and enhance the effectiveness of character-building initiatives like the Pancasila Student Profile Project.